Unifying Prolepsis And Cross-Clausal Cliticization In Lubukusu - Newkirk, Lydia (My University, 2022)
This paper examines proleptic constructions in Lubukusu (Bantu, Western Kenya). I find that Lubukusu has two distinct strategies for prolepsis: one where the extra matrix nominal is base-generated high, and one where the nominal moves from the embedded clause to the matrix position. The latter is subject to island effects, whereas the former is not. I propose an analysis for these two kinds of prolepsis based on these facts, dependant on the particularities of what nominals can be licensed in what syntactic positions in Lubukusu, and explore the cross-linguistic implications of this analysis.
Keywords: Lubukusu; proleptic constructions; Prolepsis